Character Education-Based Modules in Indonesian Language Learning to Improve Student Learning Outcomes in Elementary Schools - Nurhamimah Rambe; Wina Mariana Parinduri; Renni Ramadhani Lubis (Institut Agama Islam Negeri Palopo, 2023)
The research aims to develop a character education-based module. This research is research and development. The research uses the ADDIE development model which consists of analysis, design, development, implementation, and evaluation. The research was carried out at SD Negeri 050660 Kwala Bingai. The research subjects were 20 fifth grade students, consisting of 8 male students and 12 female students. The research object is a character education-based module. Data collection techniques are observation, tests and questionnaires. Based on the validation results of language experts with a percentage of 80.00%, they are categorized as feasible, the validation results of material experts with a percentage of 94.75% are categorized as very feasible, and the validation results of media experts with a percentage of 90.60% are categorized as very feasible. The results of the pretest were with a percentage of 47%, 2 students who completed and 18 students who did not complete. Meanwhile, the posttest trial with a percentage of 82%, 19 students completed and 1 student did not complete. Based on the validation results and trial results, it was concluded that the character education-based module was very feasible and effective for use for class V students at SD Negeri 050660 Kwala Bingai.